Influence of Physiological and Environmental Factors on Groundnut Seed Development, Quality and Storage : An Overview - PC NAUTIYAL; SHIV K YADAV (Seed Research, 2026)
One of the major considerations to attain food security is the use of quality seed which helps in higher production per unit area. Good quality seed is better in terms of genetic purity, physiological maturity and free from seed borne diseases and disorders. Production of better quality seeds starts effective and efficient flowering, pollination and fertilization to seed development is a challenge for increasing food demand. Being an oil seed, groundnut losses its viability soon and seed quality is affected during pre and post harvest periods. Though, the initial seed quality and storage environment are the two major factors to maintain viability and vigour during storage, the invasion of fungal pathogen also play a major role in decreasing the shelf life of a seed. This review article tries  to give an insight into groundnut seed development with regards to maintenance of seed quality. Further, points forefront in the seed industry related to seed longevity, seed vigour, seed priming and maintenance breeding for improving crop productivity under various biotic and abiotic stresses have been addressed.